2010
DOI: 10.1111/j.1740-0929.2010.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of an SNP marker in exon 24 of a class 3 phosphoinositide‐3‐kinase (PIK3C3) gene with production traits in Duroc pigs

Abstract: A C↔T single nucleotide polymorphism (SNP) on exon 24 of the porcine class 3 phosphoinositide-3-kinase (PIK3C3) gene is considered a possible genetic marker for selecting backfat (BF) thickness and carcass fat, although only one study has published results on its effects by performing experiments on a single resource family. We analyzed the association of this PIK3C3 polymorphism with production traits in 739 Duroc pigs. The C allele frequency was 67.9% in our study population. PIK3C3 polymorphism showed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Moreover, CDH19 was evidenced as a copy number alterations (CNAs) target gene to impact central nervous system. ZWINT (ZW10 interacting protein PIK3C3), PIK3C3 (phosphoinositide-3-kinase class 3) and PTGS2 (prostaglandin-endoperoxide synthase 2) were important for cell proliferation [60][62], and PIK3C3 and PTGS2 were proved as candidate marker for production and reproductive traits in pigs [63][65]. These findings indicated that CNVs may have potential effect on immune response, production and reproductive traits of these pigs.…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, CDH19 was evidenced as a copy number alterations (CNAs) target gene to impact central nervous system. ZWINT (ZW10 interacting protein PIK3C3), PIK3C3 (phosphoinositide-3-kinase class 3) and PTGS2 (prostaglandin-endoperoxide synthase 2) were important for cell proliferation [60][62], and PIK3C3 and PTGS2 were proved as candidate marker for production and reproductive traits in pigs [63][65]. These findings indicated that CNVs may have potential effect on immune response, production and reproductive traits of these pigs.…”
Section: Resultsmentioning
confidence: 88%
“…The data collection method used was that described by Hirose et al . (, ). Population selection traits included average daily gain (ADG), BF, loin EMA, and intramuscular fat content (IMF).…”
Section: Methodsmentioning
confidence: 99%
“…Another candidate gene, acyl-CoA dehydrogenase, C-4 to C-12 straight chain gene [ACADM), was tested, but no association with fat deposition was detected (Kim et al, 2006). Instead, SNP C2604T on exon 24 in phosphoinositide-3-kinase, class 3 gene {PIK3C3) was reported as a candidate DNA marker for fatness traits in an experimental cross of Korean native boars and Landrace breeds (Kim et al, 2005a) and Dtiroc breeds (Hirose et al, 2011). Lee et al (2006) proposed member RAS oncogene family gene {RAB31), vesicle-associated membrane protein, associated protein A gene {VAPA), and 7V-ethylmaleimide-sensitive factor attachment protein ^ gene (NAPG) as candidate genes because these gene loci are close to SW71 and related to the physiological functions of GLUT4.…”
Section: Introductionmentioning
confidence: 98%